Endoscopic dilatation for benign oesophageal strictures in infants and toddlers: Experience of an expectant protocol from North African tertiary centre - Sherif M.K Shehata; Mohamed E Enaba (Wolters Kluwer Medknow Publications, 2012)
Purpose: The purpose of this study was to present the safety and effectiveness of an expectant protocol employing Savary-Gilliard dilatation in benign oesophageal stricture in infants and toddlers along a decade of experience. Patients and Methods: Thirty eight infants and toddlers with benign oesophageal stricture with age ranged between 5 and 22 months were treated by modified dilatation protocol. Complications and outcomes of the dilatation protocol were reported during a follow-up period of 12 to 100 months. Results: We have 25 cases of corrosive stricture, 4 congenital, 4 post-reflux and 5 post-anastomotic strictures. A total of 654 dilatations in 265 sessions were done. The corrosive subgroup has a mean dysphagia score of 2.6 pre-dilatation that improved at 6 months after end of dilatation to a mean of 0.3. In the non-corrosive subgroup, significant lower number of dilatation and sessions were reported. We have three failures that need surgery. Thirty five cases reach acceptable oesophageal caliber. Mucosal tear and small perforation each reported once. Small diverticulum reported twice. Conclusions: The expectant dilatation protocol is feasible in managing benign oesophageal stricture in infants and toddlers without increasing the morbidity. It is effective even in long segment or multiple corrosive strictures.